Determinação Simultânea de Lipídios Neutros e Polares em Zooplâncton por Espectroscopia de Fluorescência Sincrônica e Calibração Multivariada - Caiana, Elizeu Cordeiro (2015)
Life support in various ecosystems is made possible by a group of organisms, called primary producers. Because they are mostly photoautotrophic, these individuals secure the middle nutrients (in higher carbon part) through the process of photosynthesis. In aquatic ecosystems phytoplankton (microalgae) is responsible for most of the primary production. As a link between individuals of the first trophic level and individuals of higher trophic levels are the organisms belonging to the zooplankton. Thus, the study of the biochemical composition of the zooplankton community can be used as an indicator of nutritional status in aquatic ecosystems. Thus, this study aimed to build PLS multivariate calibration models for the simultaneous spectrofluorimetric determination of neutral and polar lipid classes. In order to simplify the procedures involved in the construction of models, commercial standards were used to perform the calibration mixtures. These solutions were previously defined by conducting a Brereton mixture design of three levels and two factors. In a preliminary step, the models built were used to predict the concentrations of the two commercial lipids, triolein (TO) and phosphatidylcholine (PC), a set of external standards. In evaluating the performance parameters related to this step, it was observed that the models were in an acceptable condition for application to real samples. However, when evaluating the synchronous fluorescence spectra of the samples (macro and mesozooplankton), it was observed that máx the band corresponding to the neutral lipids varies between samples, so that the proposed method can not be applied to real system.